Protein refinement with GSAS-II - Von Dreele, Robert (Powder diffraction, 2019)
The General Structure Analysis System (GSAS)-II software package is a fully developed, open source, crystallographic data analysis system written almost entirely in Python. For powder diffraction, it encompasses the entire data analysis process beginning with 2-dimensonal image integration, peak selection, fitting and indexing, followed by intensity extraction, structure solution and ultimately Rietveld refinement, all driven by an intuitive graphical interface. Significant functionality of GSAS-II also can be scripted to allow it to be integrated into workflows or other software. For protein studies, it includes restraints on bond distances, angles, torsions, chiral volumes and coupled torsions (e.g. Ramachandran Φ/Ψ angles) each with graphical displays allowing visual validation. Each amino acid residue (and any ligands) can be represented by flexible rigid bodies with refinable internal torsions and optionally fully described TLS thermal motion. The least-squares algorithm invokes a Levenberg-Marquart minimization of a normalized double precision full matrix via Singular Value Decomposition providing fast convergence and high stability even for a large number of parameters. This paper will focus on the description of the flexible rigid body model of the protein and the details of the refinement algorithm.